Pengaruh Suplementasi Madu Trigona terhadap Parameter Fungsi Hati dan Ginjal Tikus Albino (Rattus norvegicus) yang Diberikan Simvastatin: Effect of Trigona Honey Supplementation on Liver and Kidney Function in SimvastatinAdministered Albino Rats (Rattus norvegicus) - Mamada, Sukamto Salang; Usmar, Usmar; Aliyah, Aliyah; Aminullah, Aminullah; Rahayu, Ayu Indah; Hidayat, Khaldun; Salampe, Mirnawati (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2018)
Simvastatin is a drug acting on 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase enzyme leading to decrease of lipid level in plasma. Simvastatin is associated with pleiotropic effects such as cardioprotective, hepatoprotective, and nephroprotective effect. This study aimed to observe effect of supplementation of trigona honey on parameters of liver function (SGPT and SGOT) and kidney function (urea) in albino rats (Rattus norvegicus) given 40 mg/kg simvastatin. Twenty-four male albino rats were divided into 6 groups (n=4). Each group was administered different treatments for 15 days orally. Group I was put as health control without any treatment, group II was given sodium carboxymethylcellulose (1% b/v) as negative control, group III was given simvastatin at the dose of 40 mg/kg, group IV was administered simvastatin (40 mg/kg) and trigona honey (6.5% v/v), while group V and VI were administered simvastatin (40 mg/kg) and ubiquinone (1.43 mg/kg); and simvastatin (40 mg/kg), trigona honey (6.5% v/v), and ubiquinone (1.43 mg/kg), respectively. Upon the treatments, level of SGOT, SGPT, and ureum was determined. The data were analyzed by using Analysis of Variance (ANOVA) and Least Significant Difference tests (p=0.05). According to the analysis, it was concluded that supplementation of trigona honey in rats administered simvastatin showed significantly lower level of all parameters than groups of simvastatin and controls.